Mıtochondrial DNA and cancer - (:unkn) unknown (My University, 2007)
Mitokondriyal DNA' nın, nükleer DNA' ya kıyasla mutasyonlara daha duyarlı olması ve tamir mekanizmalarının sınırlılığı nedeniyle karsinogenezde rol aldığı öne sürülmüştür. Bu derlemede tiroid, kolorektal, meme ve gastrik kanserlerde, mitokondriyal genom kararsızlığı, mitokondriyal DNA mutasyonlarının apoptozis ile ilişkisi ve mitokondriyal genomdaki değişimler değerlendirilmiştir

Mitochondrial DNA has been proposed to be involved in carcinogenesis because of high susceptibility to mutations and limited repair mechanisms in comparison to nuclear DNA. In this paper, we review mitochondrial genome instability, relation of mitochondrial DNA mutations with apoptosis and mitochondrial genomic aberrations reported in solid tumors of the thyroid, colorectal, breast, and gastric cancers.
mitokondriyal DNA ve kanser
Keywords: Genel ve Dahili Tıp